Services Marketing Development: Employees Service Orientation and Service Quality in the Telecommunication Sector - Molochny, Boris (Marketing & Menedzsment, 2019)
Marketing strategies play central role in achieving competitive superior values mostly in customer’s perceptions and minds. Over the course of the development of the industry, in the transition from a period of rapid growth to more moderate growth, expressed in a slowing of the rate of technological innovation and applications, the results off business activity and loss off market segment indicate a transition to a stage of sector maturation. The current report is based on comprehensive research off telecommunication sector. The authors investigated the proposed model in two modes: 1) single service provider to multiple business customers (B2B) relationships, and 2) multiple service providers , copper fines infrastructure company and cable infrastructure company to consumers (B2C) relationships.